THE IMAGE OF AN ARTIST AS A LITERARY-AESTHETIC PHENOMENON - I.V. Devdyuk; S.I. Nisevych (Vasyl Stefanyk Precarpathian National University, 2015)
The article deals with the literary essence of the concept of the image of an artist in the imagery system of the work of art. It is defined that according to the level of generalization the image of an artist can be referred to the literary type, as it concentrates in itself the most essential traits and the outlook of the creative individuals of the time, at the same time demonstrates its uniqueness and originality. Depending on the perspective of the study it can be seen both as an image-character and image-personage.